The impact of focused attention on subsequent emotional recollection: A functional MRI investigation. (17th February 2020) - Dolcos, Florin; Katsumi, Yuta; Bogdan, Paul C.; Shen, Chen; Jun, Suhnyoung; Buetti, Simona; Lleras, Alejandro; Bost, Kelly Freeman; Weymar, Mathias; Dolcos, Sanda
Abstract: In his seminal works, Endel Tulving argued that functionally distinct memory systems give rise to subjective experiences of remembering and knowing (i.e., recollection- vs. familiarity-based memory, respectively). Evidence shows that emotion specifically enhances recollection, and this effect is subserved by a synergistic mechanism involving the amygdala (AMY) and hippocampus (HC). In extreme circumstances, however, uncontrolled recollection of highly distressing memories may lead to symptoms of affective disorders. Therefore, it is important to understand the factors that can diminish such detrimental effects. Here, we investigated the effects of Focused Attention (FA) on emotional recollection. FA is an emotion regulation strategy that has been proven quite effective in reducing the impact of emotional responses associated with the recollection of distressing autobiographical memories, but its impact during emotional memory encoding is not known. Functional MRI and eye-tracking data were recorded while participants viewed a series of composite negative and neutral images with distinguishable foreground (FG) and background (BG) areas. Participants were instructed to focus either on the FG or BG content of the images and to rate their emotional responses. About 4 days later, participants' memory was assessed using the R/K procedure, to indicate whether they R ecollected specific contextual details about the encoded images or the images were just familiar to them – i.e., participants only K new that they saw the pictures without being able to remember specific contextual details. First, results revealed that FA was successful in decreasing memory for emotional pictures viewed in BG Focus condition, and this effect was driven by recollection-based retrieval. Second, the BG Focus condition was associated with decreased activity in the AMY, HC, and anterior parahippocampal gyrus for subsequently recollected emotional items. Moreover, correlation analyses also showed that reduced activity in these regions predicted greater reduction in emotional recollection following FA. These results demonstrate the effectiveness of FA in mitigating emotional experiences and emotional recollection associated with unpleasant emotional events. Highlights: Emotion control through Focused Attention (FA) reduces emotional experience. FA also reduces subsequent emotional memory, by impacting recollection. FA reduces activity in the amygdala and medial-temporal lobe (MTL) memory regions. Individual differences modulate recollection-based retrieval in amygdala and MTL. FA is an efficient strategy in reducing unwanted emotional experience and memory.